The role of nurses in the management of atopic dermatitis: Results of an international survey - Hélène Aubert; Kathrin Thormann; Sebastien Barbarot; Pavel Chernyshov; Meete Deleuran; Maya El‐Hachem; Jette deGroot; Danielle Marcoux; Dagmar Simon; Florine Raymakers; Jean‐François Stalder (Wiley, 2022)
Abstract Background Atopic dermatitis (AD) is a chronic inflammatory skin condition that has a major impact on the quality of life of patients and their families. Therapeutic patient education (TPE) is recommended for all patients with this condition to improve disease management, adherence to therapy, and quality of life. Nurse‐led consultation, when performed by expert nurses, can be as effective as consultation by dermatologists in this field. Objective This study aimed to examine the role of nurses in the management of patients with atopic dermatitis. Methods A global survey was carried out to determine the current role of nurses in TPE for patients with AD. A 24‐item online questionnaire was sent to all members of the ISAD‐OPENED network. Results In total, 85 health care professionals from 20 countries answered the questionnaire. About 75% of the responding physicians and nurses reported effective interprofessional collaboration. The collaboration between nurse and physician was deemed to be excellent by 51% of the respondents. According to caregivers, a trained nurse could be helpful in many other fields, such as nurse consultations, patient care demonstrations, telephone follow‐ups between consultations, and patient workshops. The main obstacles preventing nurse involvement in TPE are insufficient training of nurses, lack of recognition, and lack of specific funding. Conclusion This study emphasises the potential of the help provided by trained nurses throughout the TPE process. Doctor/nurse teams are very promising for TPE in the field of AD because of their potential to improve patient care.